1998
DOI: 10.1177/002215549804600601
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease-Gold Labels Heparin in Human Mast Cell Granules: New Use for an Ultrastructural Enzyme Affinity Technique

Abstract: We evaluated an enzyme affinity-gold ultrastructural technique designed to identify RNA-rich structures, based on an RNase-gold (R-G) probe in human mast cells (HMCs). As expected, the R-G technique labeled RNA-containing ribosomes and nucleoli in HMCs. The heparin-rich secretory granules in HMCs were also labeled. Extensive studies revealed that HMCs isolated from lung or skin and sustained in short-term cultures, derived de novo in growth factor-supplemented cord blood cell cultures, or present in vivo in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 46 publications
(66 reference statements)
3
26
0
Order By: Relevance
“…RNase digestion of sections prior to immunogold labeling resulted in a marked reduction in the immunogold labeling in nuclei and granules, indicating that the labeling, for the most part, represents RNA. The failure to completely remove RNA with ribonuclease is consistent with previous studies [15,44]. Similarly, in human eosinophils, use of DNase I and RNase prior to DNA immunostaining and RNA staining with molecular probe resulted in marked reduction in DNA and RNA fluorescent signals in both nuclei and granule compartments, suggesting the specificity of our staining procedures.…”
Section: Discussionsupporting
confidence: 88%
“…RNase digestion of sections prior to immunogold labeling resulted in a marked reduction in the immunogold labeling in nuclei and granules, indicating that the labeling, for the most part, represents RNA. The failure to completely remove RNA with ribonuclease is consistent with previous studies [15,44]. Similarly, in human eosinophils, use of DNase I and RNase prior to DNA immunostaining and RNA staining with molecular probe resulted in marked reduction in DNA and RNA fluorescent signals in both nuclei and granule compartments, suggesting the specificity of our staining procedures.…”
Section: Discussionsupporting
confidence: 88%
“…3). All of these morphological observations informed our pursuit of a possible synthetic role for HMC cytoplasmic granules [24, 25, 26, 27, 28, 29, 30]. These recently published studies in aggregate suggest that HMC granules are equipped for such a role, and they considerably augment our vision of the role of secretory-storage granules in the cell biology of all granulated secretory cells.…”
Section: Introductionmentioning
confidence: 82%
“…Where morphological reviews are available, they are cited without extensive recapitulation. Rather, we draw attention to newer studies of HMC organelles and their possible functional relationships to eicosanoid [16, 17], cytokine [18, 19, 20, 21, 22, 23], and RNA biology [24, 25, 26, 27, 28, 29, 30]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, well-known constituents of ZG such as RNAse A and carboxyl ester lipase (CEL) have the potential to interact with proteoglycans, e.g. to influence enzyme function (Dvorak & Morgan 1998, Rebaï et al 2005. Moreover, an interaction of the secretory lectin ZG16p (Cronshagen et al 1994, Kleene et al 1999) with heparan sulfate containing proteoglycans from ZG has recently been reported (Kumazawa-Inoue et al 2012).…”
Section: The Formation Of Zg In the Acinar Cells Is Initiated At The mentioning
confidence: 99%